Pediatric emergency asthma presentations in Southwest Victoria: a retrospective cross-sectional study 2017 to 2020. (1st February 2022) - Terry, Daniel; Peck, Blake; Kloot, Kate; Hutchins, Toinette
Abstract: Objectives: Australia has one of the highest prevalence of asthma globally, and accessible emergency asthma presentation data remains vital, however, is currently underreported in regional and rural areas. Utilizing the Rural Acute Hospital Data Register (RAHDaR) which includes previously non-reported data, the aim of the study is to provide a more accurate understanding of asthma emergency presentation events, while investigating the factors associated with these presentations. Methods: A retrospective cross-sectional study collected de-identified emergency asthma presentation data from nine health services in regional Victoria for children aged 0 to 14 years between 2017 and 2020. Demographic and presentation data were collated along with government datasets. Asthma emergency presentations incidence rates and predictor variables were analyzed using hierarchical multiple regression after adjusting for smoking and sex. Significance was determined at p < 0.05. Results: Of the 1090 emergency asthma presentations, n = 369 occurred at health services who did not previously report data. This represents a 33.86% increase in our understanding of emergency asthma presentations and demonstrating a rate of 16.06 presentations per 1000 children per year. Key factors such as age, population density, and private health insurance were associated with asthma emergency presentation events among both sexes, while socioeconomic status and rurality were not predictive. Conclusions: Although some findings are consistent with current research, the study highlights previously unrecognized specific factors that are predictive of asthma among 0–14-year-old children. These findings provide more accurate insights for healthcare workers and policymakers as they seek to support people with asthma and accurately address health inequities.